Implementation of HIV non-occupational post-exposure prophylaxis for men who have sex with men in 2 cities of Southwestern China. Issue 43 (29th October 2021) - Wu, Yufei; Zhu, Qiuying; Zhou, Yuejiao; Liang, Shujia; Li, Rongjian; Liang, Nengxiu; Li, Chunying; Lan, Guanghua
Abstract : Abstract: Non-occupational post-exposure prophylaxis (nPEP) has often relied on the joint work of emergency physicians and infectious disease specialists in busy emergency departments and human immunodeficiency virus (HIV)/sexually transmitted infections clinics abroad, where adherence education and follow-up are invariably reactive. In our pilot study, community-based organizations (CBOs) were invited to together implement the nPEP tailored to men who have sex with men (MSM) in 2 cities of Guangxi in Southwestern China, of which experiences and lessons drawn from would be provided to the promotion of nPEP in China. The study population enrolled MSM individuals prescribed nPEP from September 2017 to December 2019. One-to-one follow-ups by CBOs were applied through the treatment. Predictors of treatment completion were assessed by logistic regression. Of 271 individuals presented for nPEP, 266 MSM with documented treatment completion or non-completion, 93.6% completed the 28-day course of medication. Completion was associated with reporting side effects (aOR = .10; 95% CI: 0.02–0.38; P = .001). The follow-up rate of 91.9% was achieved based on the definition of loss to follow-up. No documented nPEP failures were found, although 1 MSM subsequently seroconverted to HIV due to ongoing high-risk behavior. CBOs' engagement in HIV nPEP, especially the "one-to-one" follow-up supports by peer educators partly ensure adherence and retention to nPEP. Tailored interventions are needed to address the subsequent high-risk behaviors among the MSM population.